If 2tanA = 3tanB, prove that tan(A-B) = (sin2A)/(5-cos2B)
Answers
Answered by
12
tan(A-B) = (tanA - tanB)/(1 + tanAtanB)
= (3/2 tanB - tanB)/(1 + 3/2 tanBtanB) ... given 2tanA = 3tanB
= tanB(3/2 - 1)/(1 + 3/2 tan2B)
= tanB (1/2)/(sec2B - tan2B + 3/2 tan2B) .. since 1 + tan2B = sec2B
= tanB (1/2)/(sec2B + 1/2 tan2B)
= sinB cosB/(2 + sin2B)
= 2sinB cosB/(4 + 2sin2B)
= sin2B /(4 + 1 - cos2B) .... 2sin2B = 1 - cos2B
= sin2B /(5 - cos2B)
= (3/2 tanB - tanB)/(1 + 3/2 tanBtanB) ... given 2tanA = 3tanB
= tanB(3/2 - 1)/(1 + 3/2 tan2B)
= tanB (1/2)/(sec2B - tan2B + 3/2 tan2B) .. since 1 + tan2B = sec2B
= tanB (1/2)/(sec2B + 1/2 tan2B)
= sinB cosB/(2 + sin2B)
= 2sinB cosB/(4 + 2sin2B)
= sin2B /(4 + 1 - cos2B) .... 2sin2B = 1 - cos2B
= sin2B /(5 - cos2B)
Similar questions
Computer Science,
9 months ago
Computer Science,
9 months ago
English,
1 year ago
Chemistry,
1 year ago
Biology,
1 year ago